2020
DOI: 10.1111/eje.12523
|View full text |Cite
|
Sign up to set email alerts
|

Empathy of dental students towards children after behaviour guidance lectures and clinical experience

Abstract: IntroductionThe empathetic behaviour of dentists is essential for perfect patient care. Because the behaviour of child patients in a dental clinic differs from that exhibited by the adults, knowing of empathy of dental students towards the child in the dental clinic is an important concern.MethodsWe distributed a modified form of the Health Professions Student version (HPS‐version) of the Jefferson Scale of Empathy (JSE) to dental students in two rounds: (R1) before and (R2) after introducing behaviour guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The TEQ exhibited good internal consistency (α = 0.87) and high test-retest reliability (0.79 and 0.73, respectively). The items were regarding emotional contagion (1,4), emotional assessment (2,7,10,12,15), empathetic response (13), emotion comprehension (8), sympathetic physiological arousal (3,6,9,11), and altruism (5,14,16). Empathy was assessed with a five point Likert scale ranging from "never" to "always".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEQ exhibited good internal consistency (α = 0.87) and high test-retest reliability (0.79 and 0.73, respectively). The items were regarding emotional contagion (1,4), emotional assessment (2,7,10,12,15), empathetic response (13), emotion comprehension (8), sympathetic physiological arousal (3,6,9,11), and altruism (5,14,16). Empathy was assessed with a five point Likert scale ranging from "never" to "always".…”
Section: Methodsmentioning
confidence: 99%
“…9 Authors suggest that such problems can be overcome by lifelong and continuous education of health care professionals as well as by incorporating better training programs with greater emphasis on behavioral sciences and ethics. 11,12 While some authors are also of the view that empathy decline is an unavoidable psychological effect. 13 The concern was captioned by one of the authors as: "How can we stop the rot?"…”
Section: Introductionmentioning
confidence: 99%
“…Various mindfulness-based training programmes have successfully increased empathy levels (Gur & Yilmaz, 2020;Winning & Boag, 2015). Further, simulated practice exercises are found to be effective to develop empathy in medical contexts (Bearman et al, 2015), whereas other formats such as behavioural guidance teaching where students are taught about the behaviour of their patients are unsuccessful (Souror et al, 2020). To enhance engagement in simulations, virtual reality (VR) technology is often adopted and, by virtue of VR's immersive nature, allows individuals to engage in perspective-taking more readily (Schutte & Stilinovic, 2017).…”
Section: Format Of Empathy Interventionmentioning
confidence: 99%
“…10 Recognising the significance of this dramatic drop in empathy, healthcare curricula seek to impart empathy as a core attribute for the next generation of healthcare professionals. 16 Whilst there is no agreed format with which to best foster empathy, there are three imperative factors that are believed to constitute empathy: "perspective-taking," "compassionate care" and "walking in the patients' shoes" and these account for the development of a metacognitive side when interacting with patients. 17 There are examples of good practice with various approaches, ranging from the use of an E.M.P.A.T.H.Y tool to improve doctorpatient communication, 18 through to the use of video clips about patient encounters to achieve sustainable increases in empathy score amongst medical students.…”
Section: Introductionmentioning
confidence: 99%
“…For dental students, it has been suggested that this decline could be attributed to a focus on the more technical demands of intensive training and the curriculum at dental schools being more procedurally focused rather than patient‐centred 10 . Recognising the significance of this dramatic drop in empathy, healthcare curricula seek to impart empathy as a core attribute for the next generation of healthcare professionals 16 . Whilst there is no agreed format with which to best foster empathy, there are three imperative factors that are believed to constitute empathy: “perspective‐taking,” “compassionate care” and “walking in the patients’ shoes” and these account for the development of a metacognitive side when interacting with patients 17 …”
Section: Introductionmentioning
confidence: 99%